BUDAYA FILANTROPI ISLAM PADA BMT SEBAGAI WADAH BISNIS BERBASIS ISLAM - Despileny, Iren; Nurnasrina, Nurnasrina (Jurnal Ekonomi Bisnis Kompetif, 2024)
Organizational culture in Islamic philanthropy is a reflection of Islamic values, principles, and ethics that are carried out in various charitable and social activities. Islamic philanthropic organizations have a mission to help the community, especially the underprivileged, by distributing resources fairly and sustainably. Through descriptive research with a sample of 100 BMT members in Pekanbaru, the results showed that the culture of Islamic philanthropy is interpreted in the criteria of good enough to good, this indicates that the culture of Islamic philanthropy that has been running in BMT can be said to be quite good even though there must still be continuous evaluation to improve improvement and perfect the culture in an Islamic manner. Keywords: Organizational Culture, BMT, Islamic Philanthropy